INTRAMOLECULAR SH2' MACROCYCLIZATIONS - Baldwin, J; Adlington, R; Mitchell, M; Robertson, J (1991)
The synthesis of 10-15 membered α-methylene macrocyclic lactones from the functionalised allylstannanes (7e)-(7j) is described. Attempts to synthesise analogous 6-9 membered lactones proved unsuccessful, resulting instead in the production of dilactones and AIBN derived adducts. © 1991.